(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
One of the urgent problems of today is environmental pollution with industrial waste. A small part of industrial waste is processed, it is very important to use it in other areas [1]. Artificial stone based on Portland cement is one of the most important building materials, but the high risk of discoloration over time limits its use [2]. Metakaolin, nano-SiO2 and basalt powder were used in this work as inhibitory mineral additives in Portland cement stone to prevent tarnishing. The opacification of cement stone has been studied in terms of hydration products and pore structure [3]. Both the morphology and phase assembly of the fading substance were studied at different scales using optical microscopy, laser confocal novel spectroscopy, and SEM [4]. The results show that the addition of nano- SiO2 and metakaolin can effectively slow cement stone fading as an inhibitor due to the consumption of Ca(OH)2 during cement hydration and the reduction of total porosity [5]. On the contrary, nano-SiO2 with high reactivity and specific surface area has the least number of macropores and total porosity, the lowest capillary absorption coefficient and the best resistance to tarnish along with portlandite content [6].